2017
DOI: 10.1038/s41467-017-00200-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hepatitis B infection in a scalable hepatic co-culture system

Abstract: Hepatitis B virus causes chronic infections in 250 million people worldwide. Chronic hepatitis B virus carriers are at risk of developing fibrosis, cirrhosis, and hepatocellular carcinoma. A prophylactic vaccine exists and currently available antivirals can suppress but rarely cure chronic infections. The study of hepatitis B virus and development of curative antivirals are hampered by a scarcity of models that mimic infection in a physiologically relevant, cellular context. Here, we show that cell-culture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 53 publications
2
63
0
Order By: Relevance
“…Recently, we showed that SACC‐PHHs can be robustly and persistently infected with HBV for up to 40 days with little donor‐to‐donor variability and without suppressing innate immune signaling . Building on this work, we demonstrate here that PHHs in SACCs support long‐term HBV‐HDV co‐infection in microwell plate formats.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Recently, we showed that SACC‐PHHs can be robustly and persistently infected with HBV for up to 40 days with little donor‐to‐donor variability and without suppressing innate immune signaling . Building on this work, we demonstrate here that PHHs in SACCs support long‐term HBV‐HDV co‐infection in microwell plate formats.…”
supporting
confidence: 54%
“…Recently, we showed that SACC-PHHs can be robustly and persistently infected with HBV for up to 40 days with little donor-to-donor variability and without suppressing innate immune signaling. (19) Building on this work, we demonstrate here that PHHs in SACCs support long-term HBV-HDV co-infection in microwell plate formats. Establishing long-term HBV/HDV infection in a microscale, 384-well format is a significant improvement even over 96-well formats, as it would enable high-throughput screens in automated settings.…”
supporting
confidence: 51%
“…Pregenomic ribonucleic acid (pgRNA) in the liver of chimeric mice was quantified with the Luna Universal One‐Step RT‐qPCR Kit (New England BioLabs). The primers for WMHBV were forward primer ACCCAATGCCCCTATCTTATC and reverse primer CAGGAAGATGCTGGAGATTG, and the primers for HBV were forward primer GAGTGTGGATTCGCACTCC and reverse primer GAGGCGAGGGAGTTCTTCT …”
Section: Methodsmentioning
confidence: 99%
“…The primers for WMHBV were forward primer ACCCAATGCCCCTATCTTATC and reverse primer CAGGAAGATGCTGGAGATTG, and the primers for HBV were forward primer GAGTGT GGATTCGCACTCC and reverse primer GAGG CGAGGGAGTTCTTCT. (21)…”
Section: Quantification Of Viral Pregenomic Ribonucleic Acid From LIVmentioning
confidence: 99%
“…An important extension to using long-term hepatocytes for metabolism studies is their application to pharmacology (Winer et al, 2017, Shlomai et al, 2014 and toxicology investigations (March et al, 2015, Trask et al, 2014 for the effective integration of the data for PBPK modeling. Study 3 showed that the HepatoPac® system could be successfully infected cultures, e.g.…”
Section: Future Applications -Diseased Statementioning
confidence: 99%